What Competences Does the Regional Market of IT Specialists Want? Development and Approbation of Technology for Analysis of Current Vacancies in the Labor Market - A. E. Shukhman; L. S. Grishina; L. L. Legashev; D. I. Parfenov (Высшее образование в России)
One of the most dynamically developing industries in Russia is IT industry. The main problem of IT development is the lack of highly qualified specialists. Determining the relevant and in-demand knowledge and skills of specialists is possible on the basis of an analysis of vacancies posted on Internet job search portals. The study is aimed at development and approbation of the technology for analysis of current vacancies for IT specialists for further designing the content of additional vocational educational programs. Modern machine learning techniques such as Natural Language Processing can be used for automatic position selection based on skills in vacancies. K-means method was used in this paper for cluster analysis of hard and soft skills lists from vacancies posted on the HeadHunter website. The most popular skills have been determined such as teamwork skills, knowledge of working with databases and version control systems, as well as proficiency in English. It has been established that in 2021 the most popular programming language is JavaScript. As a result, two variants of programmer specialization were formed, hard and soft skills for each specialization were determined.